Therapy of genomic unstable solid tumours (WHO grade 3/4）in clinical stage III/IV using individualised neoantigen tumour peptides-INP trial (individualised neoantigen tumour peptides immunotherapy): study protocol for an open-label, non-randomised, prospective, single-arm trial - Ling Wang; Xia Chen; Juan Zhao; Jiaxi Tang; Wanyan Tang; Bin Liao; Weiqi Nian (BMJ Open, 2022)
Introduction Neoantigens derived from tumour somatic mutations are recognised as ideal vaccine targets. Tumour neoantigens have been studied in a wide range of tumours. Most of research on neoantigens has focused just on a unique tumour and a single mutated gene. Currently, a few studies have reported using a mixture of neoantigen peptides derived from multiple genetic mutation sites in the treatment of genomic unstable advanced solid malignancies. The trial aims to evaluate the safety and efficacy of individualised tumour neoantigen peptide mixtures in the treatment of genomic unstable advanced solid malignant tumours.Methods and analysis This is a prospective, non-randomised, open, single-centre, single-arm, phase I trial. Patients with genomic unstable advanced solid malignancies are eligible for study participations. 20 patients will be included in the trial. Through the whole exome and transcriptome sequencing analysis of the fresh blood and tumour tissues of the enrolled patients, the 20 25-33aa antigen peptides with the highest mutation scores of the patients will be screened out, and the corresponding new antigen peptides will be synthesised and prepared. Patients will be treated with their own individualised neoantigen polypeptide combined with a polypeptide adjuvant (human granulocyte-macrophage colony-stimulating factor). The primary endpoint is safety indicators, including general and specific adverse events which will be monitored continuously. Secondary endpoints are progression-free survival, objective response rate, objective duration of remission, 1-year survival rate and overall survival.Ethics and dissemination This study has received approval from the Ethics Committee of Chongqing University Cancer Hospital on 21 November 2019 (207/2019). The findings of this trial will be disseminated through national and international presentations and peer-reviewed publications.Trial registration number ChiCTR1900025364.